Gender-specific association of blood lipids and reproductive trajectory with cognitive impairment: A community based cross-sectional study from India - Khate, Kevingu; Chaudhary, Vineet; Longkumer, Imnameren; Saraswathy, Kallur Nava; Devi, Naorem Kiranmala (Frontiers in Psychology, 2023)
Background: Abnormal blood lipid levels in the general population and adverse reproductive events among women have been associated with cognitive impairment (CI). However, their relationship has not been extensively studied in community settings. Hence, this study aims to explore the association of CI with blood lipid levels in either sex and reproductive events/trajectory among women. Methods: A cross-sectional study was conducted among a North Indian rural population. A total of 808 adults were recruited through door-to-door household survey. Data on socio-demographic variables, reproductive profile of women, and cognitive impairment status were collected. Fasting blood sample was collected to estimate serum lipid profile. Multivariate logistic regression was performed to test for association. Results: The study demonstrated a lack of association between lipid profile and cognitive impairment among males. Surprisingly, low HDL-C among females was found to be protective against moderate/severe cognitive impairment. Further, menopausal women and those having five or higher live births were found to be at higher risk of CI than pre-menopausal women and those with 1-2 live births, respectively. Conclusion: The present study hints toward a gender-specific association of blood lipid levels with CI. Further, higher live births and menopause appear to be important risk factors for CI among women.